2021
DOI: 10.3389/fonc.2021.681683
|View full text |Cite
|
Sign up to set email alerts
|

CASK Silence Overcomes Sorafenib Resistance of Hepatocellular Carcinoma Through Activating Apoptosis and Autophagic Cell Death

Abstract: Hepatocellular carcinoma (HCC) patients usually fail to be treated because of drug resistance, including sorafenib. In this study, the effects of CASK in HCC were investigated using gain- or loss-of-function strategies by performing cell counting kit-8 assay, colony formation assay, flow cytometry, transmission electron microscopy, immunofluorescent confocal laser microscopy, tumor xenograft experiment and immunohistochemistry staining. The current results suggested that CASK expression was positively associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…First, an unbiased phenotypic screen does not require knowing which protein(s) or signaling pathways should be targeted to improve brain development and function in children with CASK -related disorders. Second, recently synthesized CASK inhibitors [ 133 ] may have benefit in treating gastrointestinal cancers [ 33 , 126 , 158 , 167 ] but would not help CASK -LOF neurodevelopmental disorders. In order to efficiently identify enhancers of CASK -dependent neurite-arbor morphogenesis, we developed a new method for preparation of primary neuronal cultures.…”
Section: Discussionmentioning
confidence: 99%
“…First, an unbiased phenotypic screen does not require knowing which protein(s) or signaling pathways should be targeted to improve brain development and function in children with CASK -related disorders. Second, recently synthesized CASK inhibitors [ 133 ] may have benefit in treating gastrointestinal cancers [ 33 , 126 , 158 , 167 ] but would not help CASK -LOF neurodevelopmental disorders. In order to efficiently identify enhancers of CASK -dependent neurite-arbor morphogenesis, we developed a new method for preparation of primary neuronal cultures.…”
Section: Discussionmentioning
confidence: 99%
“…RFC5 is a small subunit of replication factor and has been reported to involve in cell cycle progression ( 69 ). It is reported that downregulation of CASK could activate apoptosis and induce autophagic death through the JNK/c-Jun signaling pathway ( 70 ). HOXB6 has been reported to be associated with the occurrence of ovarian tumors ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…CASK is significantly up-regulated in hepatocellular carcinoma (HCC), and HCC patients with a high expression of CASK have low overall survival rates. At the molecular level, the knockout of CASK activates the c-Jun N-terminal kinase (JNK) pathway, whereas treatment with the JNK inhibitor SP600125 or transient transfection with JNK-targeting siRNA can significantly reduce the knockout of CASK-mediated autophagic cell death [ 103 ].…”
Section: The Biological Functions and Pathological Mechanisms Of Cask...mentioning
confidence: 99%